PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN PADA JOIN KOPI CABANG CIRENDEU - Muhammad Abubakar Fadillah; Mahnun Masadi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the effect of Service Quality (X1) and Store Atmosphere (X2) on Consumer Satisfaction (Y) at Join Kopi Cirendeu Branch. The sampling technique applied was probability sampling, with a sample size of 100 respondents determined using the Slovin formula. Data were analyzed using simple and multiple linear regression and hypothesis testing through the SPSS version 26 application. The results of the multiple regression analysis showed a regression equation of Y = 5.077 + 0.295 X1 + 0.480 X2. The results of the partial test showed that there was a significant influence between service quality on consumer satisfaction at Join Kopi Cirendeu Branch, the calculated t value was (16.205 > 1.985) with a significance value of (0.000 < 0.05). The Store Atmosphere variable also had a positive and significant effect, the calculated t value was (17.763 > 1.985) with a significance value of (0.000 < 0.05). The results of the simultaneous test show a calculated f value of (191.747 > 3.09), with a significance value of (0.000 < 0.05). Based on these results, it is concluded that the two independent variables, namely Service Quality (X1) and Store Atmosphere (X2), together have a positive and significant effect on Consumer Satisfaction (Y). Keywords: Service Quality, Store Atmosphere, Customer Satisfaction